Social and Non-social Reward Processing and Depressive Symptoms Among Sexual Minority Adolescents - Eckstrand, Kristen L.; Flores Jr., Luis E.; Cross, Marissa; Silk, Jennifer S.; Allen, Nicholas B.; Healey, Kati L.; Marshal, Michael P.; Forbes, Erika E. (Frontiers in Behavioral Neuroscience, 2019)
Sexual minority adolescents (SMA) are more likely to suffer from depression, putatively through experiences of social stress and victimization interfering with processing of social reward. Alterations in neural reward networks, which develop during adolescence, confer risk for the development of depression. Employing both social and monetary reward fMRI tasks, this is the first neuroimaging study to examine function in reward circuitry as a potential mechanism of mental health disparities between SMA and heterosexual adolescents. Eight SMA and thirty-eight heterosexual typically developing adolescents completed self-report measures of depression and victimization, and underwent fMRI during monetary and peer social reward tasks in which they received positive monetary or social feedback, respectively. Compared with heterosexual adolescents, SMA had greater interpersonal depressive symptoms and exhibited blunted neural responses to social, but not monetary, reward in socioaffective processing regions that are associated with depressive symptoms. Specifically, compared with heterosexual adolescents, SMA exhibited decreased activation in the right medial prefrontal cortex, left anterior insula, and right temporoparietal junction in response to being liked. Lower response in the right temporoparietal junction was associated with greater interpersonal depressive symptoms. These results suggest that interpersonal difficulties and the underlying substrates of response to social reward (perhaps more so than response to monetary reward) may confer risk for development of depressive symptoms in SMA.